A retrospective review of patients over 70 years of age undergoing pneumonectomy for non-small cell lung cancer: 10 years of experience, a cross-sectional study - Yildiz, Ozgur Omer; İnan, Kubilay and Aytekin Çelik, İlknur and Çınar, Eray (Journal of Surgery and Medicine, 2020)
Aim: Future projections suggest that more older people will be affected by non-small cell lung cancer (NSCLC) over the next years due to longer life expectancy and aging global population. Chronological age is used to define elderly. 70 years of age is the most commonly accepted lower limit of senescence since the majority of physiological changes occur after this age. The aim of the current study was to review demographic, epidemiological and clinical characteristics of patients over the age of 70 diagnosed with NSCLC who underwent pneumonectomy at our clinic in a retrospective manner. Methods: This cross-sectional study involved a retrospective assessment of 21 patients over 70 years of age who were diagnosed with NSCLC and underwent pneumonectomy between January 2010 and January 2020. Demographic data, symptoms, tumor types, localization of tumors, postoperative complications and stages of cancer were recorded in the database and statistically analyzed. Results: All 21 patients were male and had a mean age of 72.5 years. The presenting symptom was dyspnea in 23.8% of the patients, cough in 28.6%, hemoptysis in 19%, chest pain in 14.3% and weight loss in 4.8% of the patients and 9.5% of the cases were detected incidentally. The tumor types included squamous cell carcinoma (57.1%), adenocarcinoma (23.8%), adenosquamous carcinoma (14.3%) and large cell carcinoma (4.8%). Tumor site was the left lung in 81% and right lung in 19% of the patients. Early postoperative complications occurred in 5 (23.8%) patients. Three of these patients developed atrial fibrillation and two patients suffered hemorrhage. Postoperative tumor stages of the patients were stage 3a (47.6%), stage 2b (19%), stage 2a (14.3%), stage 1b (9.5%) and stage 1a2 (9.5%). Multidimensional scaling analysis showed an association between the type of tumor and smoking but no association was found between tumor type and family history (P=0.024, P=0.586, respectively). Conclusion: It should be kept in mind that surgical resection and even pneumonectomy which is associated with high mortality and morbidity can be successfully performed in older cancer patients through a good preoperative workup, tumor staging, assessment of the risk of mortality and the effects of comorbid conditions.